CFD Derived Results Lead to An Installation of An Overflow Technique in A Microreactor for Gas‐Phase Ethene Homo Polymerization. Issue 1 (11th December 2014) - Mayrhofer, Leonhard; Krallis, Apostolos; Wurnitsch, Christof; Paulik, Christian
Abstract The presented micro gas‐phase reactor is a very suitable tool for the investigation of polymerizations. To achieve conditions which are closer to industry an overflow is installed in the microreactor. With this setup it is now possible to have a distinct exchange of ethene during the polymerization. CFD calculations have been performed to evaluate the reactor setup and according to these results the reactor has been modified to allow an exchange of the reactor volume two times per minute. The overflow leads to a better heat removal from the growing polymer particles and supplies the active centers with preheated ethylene. The performed overflow‐polymerizations are compared with polymerizations in static conditions and the results allow deeper understanding of the polymerization kinetics on particle level in gas phase conditions.<inline-graphic xlink:href="ark:/27927/pgh3thj6p25" content-type="mren201400031-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />